COVID‐19: Prevalence evaluation of anxiety, depression, and burden in Argentine family caregivers. (1st February 2022) - Tartaglini, María Florencia; Hermida, Paula Daniela; Ofman, Silvia Deborah; Feldberg, Carolina; Heisecke, Silvina Lidia; Somale, Verónica; Caruso, Diego
Abstract: Background: Since WHO declaration of the COVID‐19 pandemic, the Argentine Ministry of Health considered pregnant women, over 60 years old adults, and people suffering from chronic diseases as cohorts at risk. In this context, older adults diagnosed with neurodegenerative diseases as well as their family caregivers were affected by radical changes in the dynamics of health care and a consequent limitation of help resources. The objective of this study is to estimate the prevalence of anxiety, geriatric depression, and burden in Argentine family caregivers within the COVID‐19 pandemic context. It also aims at evaluating the correlation between these variables. Method: Design: Non‐experimental, descriptive‐correlational study. Procedure: Between April and August 2020, an online survey was administered to 180 senescent family caregivers of both sexes, living in Argentina. Instruments: Ad‐hoc sociodemographic and psychosocial questionnaire, Generalized Anxiety Scale (GAD‐7), Yesavage Geriatric Depression Questionnaire (GDS‐VE), and Zarit Caregiver Burden Scale (Argentine validated version). Result: The study cohort mean age was 67 years old (sd = 6), 81% were women, and 56% were daugthers of the assisted family member. Regarding analyzed variables, 46% of the survey respondents presented depression, 68% caregiver burden, and 71% anxiety. A positive, moderate correlation was observed between geriatric depression and anxiety ("r": .468, p: .000). Conclusion: The results provide empirical evidence of the impact of care tasks on emotions of family caregivers within the context of the COVID‐19 pandemic. These findings invite devising necessary and possible anticipated intervention strategies, specially facing the second wave of the pandemic.